ANALISIS PERUBAHAN KERAPATAN VEGETASI MENGGUNAKAN CITRA LANDSAT-8 MULTITEMPORAL DI KABUPATEN BANDUNG BARAT - Andien - Rahmalia; Muhamad Aditya Nugraha; M Yusup; Mochammad Fauzan Mutawally; Riki Ridwana; Lili Somantri (JURNAL GEOGRAFI, 2022)
The rate of deforestation in Indonesia is known to be very fast, Indonesia is ranked third where deforestation in Indonesia reaches 1.6 -2.1 million hectares. Information about deforestation is very important to know because it is the main factor causing the destruction. This study aims to determine the vegetation density and the map of vegetation density in West Bandung Regency, West Java Province based on a web-based multitemporal time in 2015 and 2020. Which includes vegetation density with NDVI (Normalized Difference Index) value and its area in West Bandung Regency in 2015 and 2020 The data processing process uses the NDVI sturgess transformation which produces 5 classes, namely unvegetated land, very low, medium, and high. Technical analysis used is the overlay method and descriptive analysis method. The results of the research are articles that are used as sources of information related to changes in vegetation in West Bandung Regency. Changes in the level of vegetation and its area in West Bandung Regency in 2015 and 2020, namely the non-vegetated class has an area of ​​change of 151,681 Ha/year, the very low density area has an area of ​​change of 623.5 Ha, the low density area has an area of ​​change of 263.12 Ha , the area of ​​medium vegetation density has an area of ​​change of 1918.91 Ha, and the area of ​​high density has an area of ​​change of 2957 Ha. Keywords : Density of vegetation; NDVI; Landsat 8 Imagery